Manifestations of obstetric violence perceived by pregnant women during prenatal care in Primary Health Care - Talyta Sâmara Batista Ferreira; Bárbara Cerqueira Santos Lopes; Cássio de Almeida Lima; Ana Júlia Soares Oliveira; Lucineia de Pinho; Maria Fernanda Santos Figueiredo Brito; Sibylle Emilie Vogt; Marise Fagundes Silveira (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to estimate the prevalence of manifestations of obstetric violence (OV) perceived by pregnant women during prenatal care and its association with sociodemographic factors. Methods: population-based epidemiological, cross-sectional and analytical study conducted with pregnant women assisted in the Family Health Strategy in Montes Claros, Minas Gerais, Brazil, 2018/2020. A team of health professionals conducted data collection through face to face interviews. The s ociodemographic characteristics of pregnant women and the OV manifestations perceived by pregnant women were assessed. The variables were described by frequency distribution and the prevalence of the types of OV was estimated, with 95% confidence intervals. The Chi-square test was used to evaluate the associations. Results: the study included 300 pregnant women in their third trimester of pregnancy, most of whom (64.7%) were between 20 and 34 years old, had more than 8 years of schooling (84.5%) and lived with a partner (74.5%). The following prevalences of OV manifestations were estimated in prenatal care: physical (21.7%), sexual (7.0%), psychological (24.3%), and institutional (26.3%). No association was identified between the types of OV and the participants' sociodemographic characteristics. Conclusion: the findings of this study suggest the occurrence of different types of OV in prenatal care in the population investigated and point to the need to improve care practices for pregnant women in Primary Health Care.